Coping with the COVID-19 Pandemic’s Unique Challenges Associated with Medical Research: A Saudi Institution Approach - Almeharish A; Assiri AM; Alfattani A; De Vol E (Dove Medical Press, 2020)
Amani Almeharish,1 Abdullah M Assiri,2 Areej Alfattani,1 Edward De Vol1 1Department of Biostatics, Epidemiology and Scientific Computing, King Faisal Specialist Hospital and Research Center, Riyadh, Saudi Arabia; 2Department of Comparative Medicine, King Faisal Specialist Hospital and Research Center, Riyadh, Saudi ArabiaCorrespondence: Amani AlmeharishDepartment of Biostatistics, Epidemiology and Scientific Computing, King Faisal Specialist Hospital and Research Center, P.O. Box 3354, Riyadh 11211, Kingdom of Saudi ArabiaEmail aalmeharish26@kfshrc.edu.saAbstract: The spread of COVID-19 has become a significant threat to economic activity throughout the world, and it has made life particularly difficult for research institutions. According to a report published by Spain’s largest public research body, Cybermetrics Labs, King Faisal Specialist Hospital and Research Centre (KFSH&RC) is ranked first among the leading hospitals in the Arab world, and it has instituted a wide range of policy changes to accommodate researchers by providing them with additional flexibility. The aim of this project was to highlight the most prevalent COVID-related global challenges facing research institutions and describe how research protocol at KFSH&RC has been adjusted to minimize the disruption experienced by its researchers.Keywords: SARS-CoV-2, COVID-19, healthcare, disease, research, virus